Tourism in the Era of Internet of Things: Design Principles for Smart Tourism - Banh, Leonardo; Strobel, Gero (Wirtschaftsinformatik 2024 Proceedings, 2024)
The tourism industry plays a crucial role in many countries and has suffered under the global events of the last years (e.g., COVID-19, economic recession) with a decline in visitors and economic contributions. Through digitalization efforts of cities and states, smart tourism destinations use emerging technologies like the Internet of Things and Smart Services to provide rich on-site experiences for visitors, hoping to increase their competitiveness and attract new tourists. By conducting a design science research project in collaboration with a German municipality, this paper aims to explore how digital assistants should be designed in the context of smart tourism. Based on expert interviews and a multi-case study of 37 tourism apps, we were able to develop twelve key design principles for smart tourism applications, evaluated through a prototypical instantiation, to create design knowledge for the digitalization of tourism.
Keywords: Smart Tourism; Internet of Things; Design Principles; Smart City; Case Study